Pemberdayaan Politik Santri pada Pilwali di Surabaya - Mohammad Ilham (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2020)
Abstract: The purpose of this paper is to answer the question that relating the practice of political empowerment and its socialization about Pilwali in Surabaya to the students at Pondok Pesantren Sidoresmo. The results of the study inferred that the practice of political empowerment and its socialization to the students are influenced by the study of fiqh siyasah books. Santri's behavior is circumscribed by two factors namely; the first factor is that the Santri's action is very dependent on the political preferences of the kyai due to the patron-client relationship between the kyai-santri. The second factor is the santri's political behavior is not bound by the kyai's political choice as the assumption of the freedom of choice in the political sphere. Pondok Pesantren Sidoresmo is truly empowering students in choosing their political aspirations in the 2005 Pilwali in Surabaya openly and actively without any element of coercion and always adheres to Islamic criteria, in which some scholars consider that the law in electing leaders (mayors) is obligatory, and the law concerning leader's appointment is fard al-kifayah